Impact of Endodontic Problems on the Quality of Life of Patients in School Clinic Endodontic Problems on the Quality of Life - Azevedo, Anne Karollyne Lima de; Lech, Elouize; Konkel, Karen; Ferreira, Gabriela; Morandi, Hayla; Silva, Fabrício Rutz da; Amaral, Regiane Cristina do (ARCHIVES OF HEALTH INVESTIGATION, 2024)
Background: to evaluate the impact of endodontic problems on the quality of life related to oral health of patients with confirmed diagnosis of endodontic pathology, using the Oral Health Impact Profile (OHIP-14). Methods: this is a cross-sectional study carried out with patients in need of endodontic treatment seen at the outpatient clinics of two undergraduate courses in Dentistry in the years 2018 and 2019. The patients underwent detailed anamnesis and answered the OHIP-14 questionnaire. Results: the 97 patients from the UNIUV educational institution and 50 patients from the UFS educational institution were evaluated. The average age was 37 (± 13) years, 59% were women, 27% declared no income and 66% had more than 8 years of study. When associating the variables with OHIP 14 with or without impact in relation to quality of life, a statistically significant difference (chi-square) was found for sex and pain. It appears that the dimensions most affected were psychological discomfort and physical pain. Conclusions: pain of endodontic origin had an impact on the quality of life of the patients evaluated.